A Thorough Bibliometric Analysis of School Bullying Research Indexed in Scopus: Identifying Trends and Future Directions (1987-2023) - Lumiati, Sri; Maksum, Muh Nur Rochim; Ali, Mohamad; Apriantoro, Muhammad Subhi (Universitas Muhammadiyah Surakarta, 2023)
This study aims to map targeted bullying research using publications indexed in the Scopus database from 1987 to 2023. The starting year is 1987, based on findings from his Scopus database that this is the year in which the first publications about victims of bullying were found. This study uses bibliographic analysis method. Data were obtained by searching the Scopus database from 1987 to 2023 using a Boolean search engine. The search was carried out on August 5 at 11.15 WIB. Researchers used R and Rstudio, VosViewer and Microsoft Excel tools to analyze citations, document content and networks. The bibliometric analysis carried out was limited to Scopus data. Other national and international databases should have been considered in this study. This study presents a brief overview of the literature that is accessible to researchers working in both education and psychology and provides recommendations for future research.